ANALYSIS OF PRICE IMPACT AND PRODUCTION QUANTITY OF PALM OIL ON THE INCOME OF INDEPENDENT FARMERS: A CASE STUDY IN TANGGETADA DISTRICT, KOLAKA REGENCY - Purbaningsih, Yuli; Helviani, Helviani; Amin, Muhtar; Nursalam, Nursalam; Hasbiadi, Hasbiadi; Masitah, Masitah; Prihantini, Campina Ila; Juliatmaja, Aan Wilhan; Bahari, Dodi Ismundar; Taufik, Muh. Ilham (Yayasan Education and Social Center, 2024)
This research aims to determine the income of independent oil palm farmers in Tanggetada District, Kolaka Regency and to determine the influence of independent oil palm prices and production on farmers' income in Tanggetada District, Kolaka Regency. The research method used in this research is a quantitative method using secondary data and primary data. The results of the research show that the average income from oil palm farming in the research area with an average selling price of 1,935 kg with an average production of 60,711.92 kg/year, with total revenues of IDR 117,363,038.50/year with total cost of IDR 19,473,892.66/year. Farmer's income is IDR. 97,894,145.80/year. The price of palm oil has a significant effect on the income of independent oil palm farmers because the significance value is smaller than the confidence level (95%) namely (0.000 < 0.05), likewise production has a significant effect on the income of independent oil palm farmers because the significance value is smaller than The confidence level (95%) is (0.000 < 0.05), in Tanggetada District, Kolaka Regency